Staging criminality and colonial authority: the execution of thug criminals in British India - ní Fhlathúin, Máire (Manchester University Press, 2010)
This essay examines the spectacular and stage-managed mass executions carried out during the East India Company administration’s campaign against thug criminals during the 1830s. Drawing on Foucault’s concept of the execution as an occasion for the demonstration of the authority of the state, it analyses contemporary accounts of the staging and reception of colonial executions, considering them as performances that fall on the boundary between social drama and stage drama, and arguing that such events can be seen as rituals of social negotiation rather than performances of state authority of the kind suggested by Foucault.